2000
DOI: 10.1039/b000533i
|View full text |Cite
|
Sign up to set email alerts
|

Radical-chain deoxygenation of tertiary alcohols, protected as their methoxymethyl (MOM) ethers, using thiols as polarity-reversal catalysts

Abstract: The deoxygenation of tertiary alcohols can be accomplished by heating their MOM ethers in the presence of a peroxide initiator and a thiol catalyst: the proposed radical-chain mechanism is supported by EPR spectroscopic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…With the aim of extending the range of electron-donating groups DR n in the alcohol derivative 4, we turned our attention to the N-alkoxymethylpyrrolidin-2-ones (PYRM ethers), which were expected to undergo thiol-catalysed radical-chain decomposition to give the deoxy compound and 1-formylpyrrolidin-2-one 26, as shown in eqn. (7). Preliminary experiments with 1-tert-butoxymethylpyrrolidin-2-one 27 were very encouraging, since this PYRM ether afforded an essentially quantitative yield of 26 after treatment with TBST and DBPC in refluxing toluene (the gaseous isobutane produced would be lost).…”
Section: N-alkoxymethylpyrrolidin-2-ones (Pyrm Ethers)mentioning
confidence: 97%
“…With the aim of extending the range of electron-donating groups DR n in the alcohol derivative 4, we turned our attention to the N-alkoxymethylpyrrolidin-2-ones (PYRM ethers), which were expected to undergo thiol-catalysed radical-chain decomposition to give the deoxy compound and 1-formylpyrrolidin-2-one 26, as shown in eqn. (7). Preliminary experiments with 1-tert-butoxymethylpyrrolidin-2-one 27 were very encouraging, since this PYRM ether afforded an essentially quantitative yield of 26 after treatment with TBST and DBPC in refluxing toluene (the gaseous isobutane produced would be lost).…”
Section: N-alkoxymethylpyrrolidin-2-ones (Pyrm Ethers)mentioning
confidence: 97%
“…We found that shelf‐stable and easily available methoxymethyl (MOM)‐type tertiary alkyl ethers 1 d , 1 e could undergo the expected reaction to afford the desired product 3 a in 76 % and 57 % yields, respectively. Other substrates ( 1 a – c ) gave little or no trifluoromethylthiolation product (Scheme b).…”
Section: Methodsmentioning
confidence: 98%
“…Roberts shown that methoxymethyl (MOM) ethers can act as good precursors if the reduction is mediated by a thiol that acts as a polarityreversal catalyst (see Section 2.5). 154 Alternatively, trifluoroacetate derivatives of tertiary alcohols such as 167 can be deoxygenated with diphenylsilane and di-tert-butyl peroxide (Scheme 47). 155 Good yields can be obtained with a variety of tertiary alcohols and it appears that reducible groups such as epoxides, ketones and esters are untouched by these reaction conditions.…”
Section: Miscellaneous Reducing Agentsmentioning
confidence: 99%